Pengaruh Pariwisata Ikan Sakti Sungai Jernih Terhadap Pengembangan Ekowisata Lokal - Sumiarti, Elni; Yuanita, Ika (Jurnal Kajian Pariwisata Dan Perhotelan, 2024)
Tourism is one sector that is growing rapidly in its contribution to local economic growth. This study aims to explore the influence of "Jernih River Magic Fish" tourism on the development of local ecotourism in certain areas. Through a qualitative approach, data was collected through in-depth interviews with relevant stakeholders and analysis of related literature. The research results show that "Sakti Fish Sungai Jernih" tourism has had a significant impact on the local economy by increasing income and opening new jobs. However, the growth of tourism has also raised concerns about possible environmental impacts, including increased water pollution and damage to fish habitat. To maintain the sustainability of this tourism, ecotourism development measures have been proposed, such as environmental cleanup programs, environmental education, and local community participation. By implementing these recommendations, it is hoped that the "Sacred Fish of the Clear River" tourism can continue to develop as a source fsustainable income for local communities while preserving the natural environment and local culture.